An integrated approach for incorporating thermal membrane distillation in treating water in heavy oil recovery using SAGD. (December 2015) - Elsayed, Nesreen A.; Barrufet, Maria A.; El-Halwagi, Mahmoud M.
Highlights: TMD has outstanding performance when used with SAGD. TMD cost is substantially reduced when using flare gas as heating source. Treating BBD is effective using TMD for environmental purposes. Abstract: The production of heavy oil and bitumen requires unconventional methods. One such approach is steam-assisted gravity drainage (SAGD). This technology has key advantages but is characterized with substantial levels of water consumption and discharge. Therefore, there is a need for effective water treatment and reuse methods in SAGD. This paper examines the use of an emerging technology: thermal membrane distillation (TMD) as an integral part of water treatment for SAGD. Synergistic effects are exploited from heat and mass integration of SAGD and TMD. Specifically, the hot produced water and blowdown water are evaluated for treatment using TMD because of their thermal content and because of the need for high levels of purity which can be achieved by TMD. Several design configurations and scenarios are proposed and evaluated to assess the technical and economic viability of including TMD as a process in water-management systems for SAGD.